2013
DOI: 10.1371/journal.pone.0073786
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Specific Post-Transcriptional Regulation of γ-Synuclein Gene by Micro-RNAs

Abstract: γ-Synuclein is a member of the synucleins family of small proteins, which consists of three members:α, β- and γ-synuclein. γ-Synuclein is abnormally expressed in a high percentage of advanced and metastatic tumors, but not in normal or benign tissues. Furthermore, γ-synuclein expression is strongly correlated with disease progression, and can stimulate proliferation, induce invasion and metastasis of cancer cells. γ-Synuclein transcription is regulated basically through the binding of AP-1 to specific sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…miR‐204 is one of the known tumor suppressors found to modulate apoptosis and be remarkably downregulated in many types of cancers (Surgucheva, Gunewardena, Rao, & Surguchov, ). Here, we demonstrated that similar to miR‐200a, the expression level of miR‐204 was increased in differentiated PC12 cells following MPP + treatment (Figure b).…”
Section: Discussionmentioning
confidence: 99%
“…miR‐204 is one of the known tumor suppressors found to modulate apoptosis and be remarkably downregulated in many types of cancers (Surgucheva, Gunewardena, Rao, & Surguchov, ). Here, we demonstrated that similar to miR‐200a, the expression level of miR‐204 was increased in differentiated PC12 cells following MPP + treatment (Figure b).…”
Section: Discussionmentioning
confidence: 99%
“…12 MiR-885-3p could target γ-synuclein 3'-UTR and repress γ-synuclein, which may be involved in the tumor metastasis. 13 MiR-885-3p exerted its tumor suppressive effects in colon cancer via the disruption of angiogenesis. 14 MiR-885-3p could target the 3'-UTR of vitamin D receptor and contributed to the development of pressure ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the DBH rs129882 SNP maps within seed regions of miRNAs including hsa-miR-1268, hsa-miR-1268b, hsa-miR-4468 and hsa-miR-585 (by Target Scan 6.2, Lewis et al 2005). Further, hsa-miR-1268b is predominantly expressed in the brain tissue (intragenic microRNA database) and in the neuroblastoma SH-SY5Y cell line (Surgucheva et al 2013;Hinske et al 2014). Thus the putative DBH -3 ʹ UTR binding of hsa-miR-1268b and its expression in SH-SY5Y cells suggests that the C/T substitution of rs129882 could impact hsa-miR-1268b binding and affect the expression of DBH .…”
Section: Discussionmentioning
confidence: 99%